2015
DOI: 10.1039/c5mb00302d
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 and its role in metastasis – simulations of knockout and amplification of epithelial growth factor receptor and matrix metalloproteinases

Abstract: The calcium-binding signalling protein S100A4 enhances metastasis in a variety of cancers. Despite a wealth of data available, the molecular mechanism by which S100A4 drives metastasis is unknown. Integration of the current knowledge defies straightforward intuitive interpretation and requires computer-aided approaches to represent the complexity emerging from cross-regulating species. Here we carried out a systematic sensitivity analysis of the S100A4 signalling network in order to identify key control parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The lack of clinical association with S100A15 in the other two pathological types (squamous cell and small cell carcinoma) of lung cancer in the present study could be attributed to several reasons. First, the interaction between epidermal growth factor receptor and S100A family can promote angiogenesis and metastasis in a variety of cancers, whereas the percentage of EGFR mutations is relatively small in these 2 types of lung cancers [ 19 , 20 ]. Second, some S100A family members contribute to progression of squamous cell carcinomas, while others maintain the differentiated state of epithelium and contribute to a less invasive tumor type [ 21 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of clinical association with S100A15 in the other two pathological types (squamous cell and small cell carcinoma) of lung cancer in the present study could be attributed to several reasons. First, the interaction between epidermal growth factor receptor and S100A family can promote angiogenesis and metastasis in a variety of cancers, whereas the percentage of EGFR mutations is relatively small in these 2 types of lung cancers [ 19 , 20 ]. Second, some S100A family members contribute to progression of squamous cell carcinomas, while others maintain the differentiated state of epithelium and contribute to a less invasive tumor type [ 21 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“… Sensitivity of the endpoints (“Cell Survival” and “Proliferation”, encircled in the network representation Fig 1 in red and black, respectively) is calculated according to [ 38 , 39 ] and represented in red and black data points in the central plot. Each point in the central plot corresponds to one of states that differ from each other in exactly one node (recall that each node may assume a value of low or high activity).…”
Section: Resultsmentioning
confidence: 99%
“…, [ 29 , 32 , 37 , 58 , 59 ] and references therein). This information is analysed altogether as a single system and the factors that exert nonlinear control on the endpoints are studied with our network analysis program [ 38 , 39 ]. Several oncogenic proteins interact with NPM-ALK.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the S100A4 protein is known to be secreted by tumor and/or stromal cells and to support tumorigenesis by stimulating angiogenesis and promoting endothelial cell migration [26]. In addition it has been reported that S100A4 may support MMP-9 and MMP-13 gene expression [27] and also that it may enhance the activity of some MMPs, causing higher cell dissociation and cancer metastasis [28,29]. Vimentin, VIME (VIM).…”
Section: Common Interactors For Mmp2 and Mmp9mentioning
confidence: 99%